Views and experience of breastfeeding in public: A qualitative systematic review - Aimee Grant; Bethan Pell; Lauren Copeland; Amy Brown; Rebecca Ellis; Delyth Morris; Denitza Williams; Rhiannon Phillips (Wiley, 2022)
Abstract Breastfeeding rates in many Global North countries are low. Qualitative research highlights that breastfeeding in public is a particular challenge, despite mothers often having the legal right to do so. To identify barriers and facilitators, we systematically searched the qualitative research from Organisation for Economic Co‐operation and Development countries relating to breastfeeding in public spaces from 2007 to 2021. Data were analysed using the Thematic Synthesis technique. The review was registered with PROSPERO (registration number: CRD42017081504). Database searching identified 3570 unique records. In total, 74 papers, theses, or book chapters, relating to 71 studies, were included, accounting for over 17,000 mothers. Overall, data quality was high. Our analysis identified that five core factors influenced mothers' thought processes and their breastfeeding in public behaviour: legal system; structural (in)equality; knowledge; beliefs and the social environment. Macro‐level factors relating to legislation and inequality urgently require redress if breastfeeding rates are to be increased. Widespread culture change is also required to enhance knowledge, change hostile beliefs and thus the social environment in which mother/infant dyads exist. In particular, the sexualisation of breasts, disgust narratives and lack of exposure among observers to baby‐led infant feeding patterns resulted in beliefs which created a stigmatising environment. In this context, many mothers felt unable to breastfeed in public; those who breastfed outside the home were usually highly self‐aware, attempting to reduce their exposure to conflict. Evidence‐based theoretically informed interventions to remove barriers to breastfeeding in public are urgently required.